2016
DOI: 10.1002/ceat.201600045
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nucleation and Growth Mechanisms of the B Polymorph of L‐Histidine by Induction Time Measurement

Abstract: The nucleation and growth mechanisms of the B polymorph of L-histidine (L-his) in a water-ethanol system were determined based on induction time measurements. The induction times were experimentally determined at different supersaturations and correlated using the models of mononuclear and polynuclear mechanisms. The primary nucleation mechanism of the B polymorph of L-his was identified as a polynuclear mechanism and the growth mechanism was found to be a two-dimensional nucleation-mediated growth. These mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The obtained photomicrographs of the prepared crystals of forms A and B indicated that the crystals of form A exhibited rod‐like shapes consistent with those reported in previous works , , . The shape of crystals of form B appeared plate‐like like those reported in former works , , .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The obtained photomicrographs of the prepared crystals of forms A and B indicated that the crystals of form A exhibited rod‐like shapes consistent with those reported in previous works , , . The shape of crystals of form B appeared plate‐like like those reported in former works , , .…”
Section: Resultssupporting
confidence: 88%
“…Pure crystals of form A of L ‐his were produced from aqueous solution crystallization by cooling operation at 25 °C as described in previous works , , , . A saturated aqueous solution of L ‐his at 45 °C was prepared at 50 °C and then the solution was cooled rapidly to 10 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data include the solubility as a function of temperature because the solubility of L ‐his increases with temperature . There are reports of the dissolution rate of form B and the growth rate of form A of L ‐his in aqueous solution , and the nucleation and growth mechanisms of form B of L ‐his in the water‐ethanol system .…”
Section: Introductionmentioning
confidence: 99%
“…In CNT, the nucleation rate, J (/m 3 s), is described as where A is the pre-exponential factor, with unit of/m 3 s. R is the ideal gas constant. T is the nucleation temperature, with unit of K .…”
Section: Theorymentioning
confidence: 99%